Analisis Dampak Beban Kerja Terhadap Kepuasan Kerja Karyawan pada Bandara Sultan Iskandar Muda di Provinsi Aceh - Bakri, M; Rusmina, Cut; Hanum, Filia; Juwita; Zainuddin (Jurnal EMT KITA, 2024)
This research aims to investigate the impact of workload on the level of employee job satisfaction at Sultan Iskandar Muda Airport (SIM) in Aceh Province. The research population involved all employees of Sultan Iskandar Muda Airport, with 62 people selected as samples using the Slovin formula. This sample includes various divisions at Sultan Iskandar Muda Airport. The data analysis method used is linear regression. The results of the research show that the independent variable, namely workload, has a significantly positive effect on the dependent variable, namely employee job satisfaction at Sultan Iskandar Muda Airport in Aceh Province.